The Influence Of Team-Based Learning On Students' Understanding Of Patient Safety: A Literature Review - Duhu, Ludovikus; Kusumawati, Wiwik (Universitas Aisyah Pringsewu, 2025)
Patient safety is a form of health service that is safe for patients. To increase students' understanding of patient safety, teachers need to use teaching methods that are interesting to students. Team-based learning (TBL) is an active learning model in small teams that is expected to equip students with patient safety skills. This study aims to determine the effect of TBL on students' understanding of patient safety by reviewing the literature. Article searches were carried out through three databases, namely Scopus, PubMed, and Science Direct. Search results using the keywords